Femtosecond laser-controlled self-assembly of amorphous-crystalline nanogratings in silicon. (20th May 2016) - Puerto, Daniel; Garcia-Lechuga, Mario; Hernandez-Rueda, Javier; Garcia-Leis, Adianez; Sanchez-Cortes, Santiago; Solis, Javier; Siegel, Jan
Abstract: Self-assembly (SA) of molecular units to form regular, periodic extended structures is a powerful bottom-up technique for nanopatterning, inspired by nature. SA can be triggered in all classes of solid materials, for instance, by femtosecond laser pulses leading to the formation of laser-induced periodic surface structures (LIPSS) with a period slightly shorter than the laser wavelength. This approach, though, typically involves considerable material ablation, which leads to an unwanted increase of the surface roughness. We present a new strategy to fabricate high-precision nanograting structures in silicon, consisting of alternating amorphous and crystalline lines, with almost no material removal. The strategy can be applied to static irradiation experiments and can be extended into one and two dimensions by scanning the laser beam over the sample surface. We demonstrate that lines and areas with parallel nanofringe patterns can be written by an adequate choice of spot size, repetition rate and scan velocity, keeping a constant effective pulse number ( N eff ) per area for a given laser wavelength. A deviation from this pulse number leads either to inhomogeneous or ablative structures. Furthermore, we demonstrate that this approach can be used with different laser systems having widely different wavelengths (1030 nm, 800 nm, 400 nm), pulse durations (370 fs, 100 fs) and repetition rates (500 kHz, 100 Hz, single pulse) and that the grating period can also be tuned by changing the angle of laser beam incidence. The grating structures can be erased by irradiation with a single nanosecond laser pulse, triggering recrystallization of the amorphous stripes. Given the large differences in electrical conductivity between the two phases, our structures could find new applications in nanoelectronics.